Longitudinal in vivo monitoring of callus remodeling in BMP‐7‐ and Zoledronate‐treated fractures. Issue 9 (1st March 2020) - Mathavan, Neashan; Raina, Deepak Bushan; Tägil, Magnus; Isaksson, Hanna
Abstract: Pharmacological interventions that combine pro‐anabolic and anti‐catabolic drugs to treat recalcitrant fractures have shown remarkable efficacy in augmenting the regenerative response. Specifically, in rodent models of fracture repair, treatment with BMP‐7 and Zoledronate (ZA) has almost uniformally resulted in complete union. However, delayed remodeling may be problematic for ZA‐treated fractures. The increase in newly formed bone is substantial but if translated in humans, delayed remodeling may delay functional recovery. Our objective was to determine if, and to what extent, bone morphogenetic protein (BMP) (in synergistically administered BMP‐7 + ZA) can modulate the delayed hard callus remodeling caused by ZA. Callus remodeling in BMP‐7‐only and BMP‐7 + ZA‐treated osteotomies were monitored using in vivo µCT to follow the progression of healing at 6‐week intervals over 24 weeks in an open femoral fracture rat model. None of the groups recovered baseline cortical bone volumes within 24 weeks post‐osteotomy. Treatment prolonged the remodeling phase but the kinetics of remodeling appeared to differ between BMP and BMP + ZA groups. However, the mechanical characteristics were largely restored. Callus/bone volumes in BMP‐only treated fractures peaked as early as week 3 suggesting that remodeling is stimulated prematurely. However, this rate of remodeling was not maintained as BMP‐7 was found to exhibit negligible changes in callus/bone volumes between weeks 6 and 18, whereas declines in callus/bone volumes were present at these time points in the BMP‐7 + ZA group. Our findings suggest that inclusion of ZA as an anti‐catabolic agent may not be detrimental to the regenerative process despite a prolonged remodeling phase.